Designing and Making a Movement Infrastructure. (2015) - Bertol, Daniela
Abstract: The geometry and symmetry characterizing the regular and semi-regular polyhedra has a major impact in the manmade world of building systems. The geometric properties of polyhedra can be applied not only to the world of design and construction but can also be used to interpret the proportions and movement of the human body. This paper describes a computational methodology to design and build three-dimensional structures for movement practices based on the regular convex polyhedra —also called Platonic solids. A parametric approach is applied to design these structures —here defined as "movement infrastructure". Contemporary design and fabrication technologies are applied to the theories of movement by Rudolf Laban, which were introduced in the first half of the twentieth century but still have a major influence in the field of dance and human movement analysis. Prototypes have been built assembling parts fabricated using 3D printing technologies and off-the-shelf components. Such a parametric approach can be further applied to design and build a "movement infrastructure" at several scales and made of different materials, varying from private indoor home use to public outdoor settings.